Üniversite Öğrencilerinin Flört Kaygısı Düzeylerinin Çocukluk Dönemi Örselenme Yaşantıları Tarafından Yordanması - Erkek, Ahsen; Bingöl, Tuğba (Fırat University, 2025)
Flört kaygısı; temelde karşı cinsten kaçınmayla başlayan, bireyin ilişki yaşamasını zorlaştıran, özellikle üniversite öğrencilerinde görülen bir problemdir. Çocukluk dönemi örselenme yaşantıları, bireyin çocukluk yıllarında maruz kaldığı fiziksel istismar, duygusal istismar, cinsel istismar ve ihmallerdir. Temel ilişki anlayışının şekillendiği çocukluk yıllarında örselenme yaşantılarına maruz kalmak bireyin gelecekte flört kaygısı yaşayabilmesine neden olabilmektedir. Bu açıdan üniversite öğrencilerinin flört kaygısı düzeylerinin çocukluk dönemi örselenme yaşantıları tarafından yordanmasının incelenmesi bireyin ruhsal sağlığının korunması ve bireye erken müdahale için önemlidir. Araştırma grubu Doğu Anadolu’daki bir devlet üniversitesinde basit rastgele örnekleme yöntemiyle seçilen 369 üniversite öğrencisinden oluşmaktadır. Veri toplama aracı olarak Flört Kaygısı Ölçeği ve Çocukluk Dönemi Örselenme Yaşantıları Ölçeği Kısa Formu kullanılmıştır. Veriler, Bağımsız Örneklemler İçin t Testi, Tek Yönlü ANOVA ve Çoklu Regresyon Analizi ile analiz edilmiştir. Elde edilen sonuçlara göre cinsiyet, flörtün olup olmaması, algılanan sosyoekonomik düzey, duygusal istismar, duygusal ihmal yaşantıları değişkenleri flört kaygısı düzeyleri ile yüksek ve anlamlı bir ilişki vermektedir.

Dating anxiety is a problem that starts with avoidance of the opposite sex, makes it difficult for the individual to have a relationship, and is especially seen in university students. Childhood abuse experiences are physical abuse, emotional abuse, sexual abuse and neglect that the individual was exposed to during childhood. Being exposed to experiences of abuse during childhood, when the basic understanding of relationship is shaped, may cause the individual to experience dating anxiety in the future. In this respect, examining the prediction of dating anxiety levels of university students by childhood abuse experiences is important for the protection of the individual's mental health and early intervention. The research group consists of 369 university students selected by simple random sampling method in a state university in Eastern Anatolia. The Dating Anxiety Scale and Childhood Abuse Experiences Scale Short Form were used as data collection tools. The data were analyzed with Independent Samples t Test, One-Way ANOVA and Multiple Regression Analysis. According to the results obtained, the variables of gender, whether there is dating or not, perceived socioeconomic level, emotional abuse, emotional neglect experiences show a high and significant relationship with dating anxiety levels.
Prediction of University Students’ Dating Anxiety Levels by Childhood Abuse Experiences
Keywords: Psychological Counseling and Guidance (Other); Rehberlik ve Psikolojik Danışmanlık (Diğer)